Atlantic Advection Driven Changes in Glacial Meltwater: Effects on Phytoplankton Chlorophyll-a and Taxonomic Composition in Kongsfjorden, Spitsbergen - van De Poll, Willem H.; Maat, Douwe S.; Fischer, Philipp; Rozema, Patrick D.; Daly, Oonagh B.; Koppelle, Sebastiaan; Visser, Ronald J. W.; Buma, Anita G. J. (Frontiers in Marine Science, 2016)
Phytoplankton biomass and composition was investigated in a high Arctic fjord (Kongsfjorden, 79˚N, 11˚40’E) using year round weekly pigment samples collected from October 2013 to December 2014. In addition, phytoplankton dynamics supplemented with physical and chemical characteristics of the 2014 spring bloom (April –June 2014) were assessed in two locations in Kongsfjorden. The goal was to elucidate effects of Atlantic advection on spatial phytoplankton chlorophyll-a (chl-a) and taxonomic composition. Chl-a declined during the polar night to a minimum of 0.01 mg m-3, followed by a 1000-fold increase until May 28. Atlantic advection prevented sea ice formation and increased springtime melting of marine terminating glaciers. This coincided with spatial and temporal differences in abundances of flagellates (prasinophytes, haptophytes, cryptophytes, and chrysophytes) and diatoms in early spring. More flagellated phytoplankton were observed in the non-stratified central Kongsfjorden, whereas diatoms were more abundant in the stratified inner fjord. Contrasting conditions between locations were reduced when glacial melt water stratification expanded towards the mouth of the fjord, mediating a diatom dominated surface bloom at both locations. We suggest that glacial melt water governs spring bloom spatial timing and composition in the absence of sea ice driven stratification. The spring bloom exhausted surface nutrient concentrations by the end of May. The nutrient limited post bloom period (June-October) was characterized by reduced biomass and pigments of flagellated phytoplankton, consisting of prasinophytes, haptophytes, chrysophytes and to a lesser extent cryptophytes and peridinin-containing dinoflagellates.